Temperature and exudativory as drivers of the marmoset (Callithrix spp.) daily activity period. Issue 6 (18th October 2021) - Hilário, Renato R.; Silvestre, Saulo M.; Abreu, Filipa; Beltrão‐Mendes, Raone; de Castro, Carla S. S.; Chagas, Renata R. D.; De la Fuente, Maria F.; Duarte, Marina H. L.; Ferrari, Stephen F.; Passamani, Marcelo; Schiel, Nicola; Souto, Antonio; et al.
Abstract: Primates are affected by fluctuations in ambient temperatures, mostly through thermoregulatory costs and changes in the availability of food. In the present study, we investigate whether the ambient temperature and proxies of food availability affect the activity period of marmosets ( Callithrix spp.). We predicted that: (i) at colder sites, marmosets would spend more time at sleeping sites; (ii) midday resting bouts would be longer at hotter sites; (iii) the onset/cessation of activity and resting behavior at midday would be more closely related to temperature than food availability, and (iv) highly exudativorous groups would have higher total levels of resting. We compiled data on the onset and cessation of activity and the time spent resting at midday from seven marmoset studies from sites with a wide range of temperatures. We used generalized linear mixed models to verify the relationship between the dependent variables (lag between dawn and the onset of activities, lag between cessation of activities and dusk, and proportion of resting during midday) and the minimum and maximum temperatures at the respective study sites, together with proxies of food availability (exudativory rates, the amount of habitat available per individual, and net primary productivity) using each sample month as a sampling unit and the identity of the study as a categorical random factor. At colder sites and during colder months, the marmosets left sleeping trees later in the morning and ceased their activities earlier, while at hotter sites and during hotter months, they spent more time resting during midday. More exudativorous groups become active later in the morning, but also ceased their activities later. The abundance of food did not affect the timing of activities. We provide evidence that both low and high temperatures affect marmosets' activities, and that their activity period appears to be more influenced by the thermal environment than food availability. Abstract : Relationship between maximum temperature and the proportion of resting in the activity budget during midday (10:00–14:00) in the marmoset groups. The black line shows the relationship among the variables considering all the sites together, while the colored lines show the relationship within each site. Sites: Aracruz: Aracruz Celulose forest patch, ES; ARGMP: Américo Renné Giannetti Municipal Park; BBFS: Baracuhy Biological Field Station; Ibura: Ibura National Forest; Junco: Mata do Junco Wildlife Refuge; NFNF: Nísia Floresta National Forest; RBAR: Augusto Ruschi Biological Reserve. Research Highlights: Low temperatures increase the time that marmosets spent in sleeping sites. High temperatures increase resting during midday. Exudativory had less effect on overall resting levels than temperature.